Pre‐ and post‐surgical factors that predict the provision of rescue analgesia following hysterectomy. (14th August 2012) - Pinto, P.R.; McIntyre, T.; Fonseca, C.; Almeida, A.; Araújo‐Soares, V.
Abstract Background To better manage post‐surgical pain, standardized analgesic protocols allow for rescue analgesia (RA). This study seeks to determine which pre‐ and post‐surgical clinical and patient‐related factors, in addition to post‐surgical pain, may influence health care professional decisions on RA administration. Methods A consecutive sample of 185 women, submitted to hysterectomy for benign disorders, was assessed 24 h before (time 1; T1) and 48 h after (time 2; T2) surgery. At T1, baseline demographic, clinical and psychological predictors were assessed and at T2, post‐surgical pain, anxiety and RA administration were recorded. Results After controlling for post‐surgical acute pain intensity, logistic regression results revealed several pre‐surgical (T1) and surgical factors associated with post‐surgical RA: having other previous pain states [odds ratio (OR), 4.551; 95% confidence interval (CI), 1.642–12.611, p = 0.004], being anaesthetized with only general or loco‐regional anaesthesia (OR, 5.349; 95% CI, 1.976–14.483, p = 0.001) and pre‐surgical fear of immediate consequences of surgery (OR, 1.306; 95% CI, 1.031–1.655, p = 0.027). Concerning post‐surgical variables, higher pain intensity (OR, 1.591; 95% CI, 1.353–1.871, p < 0.001) and post‐surgical anxiety (OR, 1.245; 95% CI, 1.084–1.430, p = 0.002) were significantly associated with RA provision. Conclusions Health care decision making to administer RA might be influenced not only by post‐surgical pain intensity but also by pre‐surgical and surgical clinical factors, such as previous pain and type of anaesthesia. Patient‐related psychological characteristics, such as pre‐surgical fear and post‐surgical anxiety, may also play a role in decision making on RA provision. Implications for practice are discussed.